Nondihydropyridine Calcium Channel Blockers for the Treatment of Proteinuria: A Review of the Literature. Issue 10 (October 2019) - Steuber, Taylor D.; Lee, Jenna; Holloway, Amanda; Andrus, Miranda R.
Objective: To review the use of nondihydropyridine calcium channel blockers (non-DHP CCBs) for the treatment of proteinuria in diabetic and nondiabetic kidney disease.Data Sources: A search using PubMed and MEDLINE, Scopus, and Google Scholar was performed from 1964 through February 2019 using the following search terms alone or in combination: verapamil, diltiazem, non-dihydropyridine calcium channel blocker, proteinuria, albuminuria, microalbuminuria, kidney disease, renal disease .Study Selection and Data Extraction: All prospective English-language trials examining one or more non-DHP CCB for the treatment of proteinuria were evaluated.Data Synthesis: A total of 13 clinical trials examining the use of non-DHP CCBs to treat proteinuria alone or in combination with angiotensin-converting enzyme (ACE) inhibitors or angiotensin receptor blockers (ARBs) were included in the evaluation. Most studies evaluated patients with macroalbuminuria secondary to diabetes and hypertension. Verapamil was the most common agent studied. Non-DHP CCBs were effective in reducing proteinuria in diabetic kidney disease but did not reduce renal or cardiovascular outcomes in the one trial that evaluated clinical end points. They were generally well tolerated, with the most common adverse effect reported being constipation.Relevance to Patient Care and Clinical Practice: This review evaluates and summarizes the available evidence on non-DHP CCBs for treatment of proteinuria in patients with existing kidney disease.Conclusion: Non-DHP CCBs may be a reasonable therapeutic option for patients with diabetic kidney disease and persistent proteinuria despite maximum doses of ACE inhibitors or ARBs. Additionally, they may be reasonable alternatives to ACE inhibitors or ARBs if a contraindication or intolerance exists.